Prevalence of diabetic retinopathy within a national diabetic retinopathy screening service - Thomas, Rebecca L; Dunstan, Frank D; Luzio, Stephen D; Chowdhury, Sharmistha Roy; North, Rachel V; Hale, Sarah L; Gibbins, Robert L; Owens, David R (British journal of ophthalmology, 2015)
Aims Determine the prevalence and severity of diabetic retinopathy (DR) and risk factors in a large community based screening programme, in order to accurately estimate the future burden of this specific and debilitating complication of diabetes. Methods A cross-sectional analysis of 91 393 persons with diabetes, 5003 type 1 diabetes and 86 390 type 2 diabetes, at their first screening by the community based National Diabetic Retinopathy Screening Service for Wales from 2005 to 2009. Image capture used 2×45° digital images per eye following mydriasis, classified by qualified retinal graders with final grading based on the worst eye. Results The prevalence of any DR and sight-threatening DR in those with type 1 diabetes was 56.0% and 11.2%, respectively, and in type 2 diabetes was 30.3% and 2.9%, respectively. The presence of DR, non-sight-threatening and sight-threatening, was strongly associated with increasing duration of diabetes for either type 1 or type 2 diabetes and also associated with insulin therapy in those with type 2 diabetes. Conclusions Prevalence of DR within the largest reported community-based, quality assured, DR screening programme, was higher in persons with type 1 diabetes; however, the major burden is represented by type 2 diabetes which is 94% of the screened population.